2020
DOI: 10.1055/s-0040-1712860
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features and Clinical Repercussions of Supernumerary Teeth in a Multicenter Study: A Review of 518 Patients with Hyperdontia in Spanish Population

Abstract: Objectives The aim of this study was to establish the prevalence of supernumerary teeth (ST) in a sector of the population of Madrid, as well as possible complications associated with the presence of these teeth. Materials and Methods The study investigated patients (n = 28,114) who sought dental care at the Oral Surgery Service of three different centers between May 2005 and April 2018. Cases that did not present this numeric dental developmental variation were discarded, registering only those presenting ST.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
3
19
1
4
Order By: Relevance
“…They found 185 ST in the maxilla and 56 in the mandible, 153 were mesiodens and 115 were inverted. However, Brinkmann et al ( 19 ) concluded that although mesiodens were considered the most common ST, the present study found distomolars and supernumerary premolars to be the most frequently occurring.…”
Section: Discussioncontrasting
confidence: 66%
“…They found 185 ST in the maxilla and 56 in the mandible, 153 were mesiodens and 115 were inverted. However, Brinkmann et al ( 19 ) concluded that although mesiodens were considered the most common ST, the present study found distomolars and supernumerary premolars to be the most frequently occurring.…”
Section: Discussioncontrasting
confidence: 66%
“…In the present study, similar to other studies, the prevalence of supernumerary teeth was 1.2%. In white European population, In Finnish population, in Spanish population and in Bulgarian population the prevalence of supernumerary teeth were 1.6%, 2.2%, 1.84% and 1.1% respectively [39][40][41][42] . Racial variations, age differences among patients, different study protocols and diagnostic methods may explain the wide range of prevalence cited in the literature.…”
Section: Discussionmentioning
confidence: 87%
“…This was the case detected in Spain, where the majority of supernumerary teeth (78%) were impacted. 21 In people living during the Neolithic and Paleolithic era, the distance from the middle of the articular head to the central incisors was ranging from 110 to 124 mm (Heidelberg jaw). Today, it does not exceed 100 mm.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case detected in Spain, where the majority of supernumerary teeth (78%) were impacted. 21 …”
Section: Discussionmentioning
confidence: 99%